Prof. Eugenijus Meškauskas and Lithuanian Philosophy - Kapačiauskienė, Danutė (Problemos, 1990)
E. Meškauskas is the founder and the representative of Marxist philosophy in Lithuania. His conception of Marxist philosophy has shaped itself already in the time of Lithuanian Republic and independently of Soviet academic circles. The conception is constructed as a finite theory, which however is open to criticism. The basic premise of the theoretical construction states: “social life in its essence is practical”. On its turn, practice is viewed as a syncretic unity of material and spiritual world (expedient reconstruction of objective reality) and is considered as the linking chain of the two; the third member when compared to the classical understanding of the relation between consciousness and being. Such a paradigm of the world is characteristic to the modem philosophy. The above mentioned premise of Marxist philosophy predetermines its contents: it presents by itself essentially the theory of socio-historical development of social practice. That is why the paper mostly deals with the conception of socio-economical formation.